Empowering communities through university collaboration: strategies and success stories of SULAM (Service-Learning Malaysia and University for Society) in park and community design - Wan Ali@Yaacob, Wan Noor Anira (Universiti Teknologi MARA, Kedah, 2024)
University-community collaboration is increasingly recognised as a vital tool for social transformation. In Malaysia, the SULAM (Service-Learning Malaysia and University for Society) initiative is at the forefront of these efforts, particularly in Park and Community Design. This study examines the challenges and strategies involved in implementing SULAM within university settings to empower students and communities. The research addresses the underutilisation of community spaces and the lack of student engagement in practical, community-driven projects. The primary aim is to understand the effectiveness of these projects in community and park design and to evaluate their impact on students and local communities. Using a qualitative approach, this study focuses on a case study of SULAM projects in Puncak Iskandar, Seri Iskandar, Perak, Malaysia. Data collection methods, including surveys and document analysis, provide a comprehensive view of the dynamics within these partnerships and their impact on stakeholders. The study identifies key factors contributing to successful university-community collaborations, such as stakeholder engagement, cultural sensitivity, and needs-based approaches. Significant findings highlight the transformative potential of SULAM initiatives in empowering communities and promoting sustainable development. The results emphasis the reciprocal benefits of these partnerships, where students gain practical experience, and communities receive valuable support and innovative solutions. Issues like environmental conservation, public health, education, and economic growth are effectively addressed through these collaborations. In conclusion, the study underscores the pivotal role universities play in fostering social responsibility and community engagement through service learning, making a substantial impact on both students and local communities.